FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN KELELAHAN MATA PADA PEKERJA KANTOR X KARANGANYAR - Tianto, Arum Kurniawati Agnes; Qadrijati, Isna; Haryati, Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Office workers X Karanganyar are computer users, with an average duration of computer use in a day of more than 4 hours. The average worker has been working for more than three years and is still exposed to lighting intensity that is less than standard (< 300 lux) with an eighthour workday, putting them at risk of experiencing eye fatigue. This study aims to determine the relationship between lighting intensity, working period, and duration of computer use with complaints of eye fatigue in Karanganyar X Office workers. This study uses an analytical observational method with a cross-sectional approach. The research population was 80 people. The sampling technique used is purposive sampling with criteria of age 50 and working on a computer for at least 2 hours continuously, and the research sample is 45 people. Measurement of lighting intensity using a Lux meter and eye fatigue using a Visual FatigueIndex (VFI) questionnaire. The results of the bivariate analysis with Somers'd showed that there was a relationship between lighting intensity and complaints of eye fatigue (p-value = 0.030, r = 0.333), there was a relationship between years of service and complaints of eye fatigue (p-value = 0.003, r = 0.457), and there is a relationship between the duration of computer use and complaints of eye fatigue (p-value = 0.028, r = 0.326). To reduce eye fatigue, it can be done by setting up the layout of the workplace, taking breaks in between work, and getting regular eye health checks.